Patient feedback for safety improvement in primary care: results from a feasibility study. Issue 6 (21st June 2020) - Hernan, Andrea L; Giles, Sally J; Beks, Hannah; McNamara, Kevin; Kloot, Kate; Binder, Marley J; Versace, Vincent
Abstract : Objectives: Patient involvement in safety improvement is a developing area of research. The aim of this study was to investigate the feasibility of a patient feedback on safety intervention in primary care. Specifically, the intervention acceptability, fidelity, implementation enablers and barriers, scalability, and process of systematically collecting safety data were examined. Design, setting and participants: Mixed-methods feasibility trial with six purposively selected Australian primary care practices. Intervention: The intervention comprised an iterative process with a cycle of measurement, learning, feedback, action planning and implementation period of 6 months. Primary and secondary outcomes: Qualitative and quantitative data relating to feasibility measures (acceptability, fidelity, enablers, barriers, scalability and process of collecting safety data) were collected and analysed. Results: A total of n=1750 patients provided feedback on safety. There was a statistically significant increase in mean patient safety scores indicating improved safety (4.30–4.37, p=0.002). Staff deemed the intervention acceptable, with minor recommendations for improvement. Intervention fidelity was high and implementation enablers were attributed to the intervention structure and framework, use of intuitive problem-solving approaches, and multidisciplinary team involvement. Practice-based safety interventions resulted in sustainable and measurable changes to systems for safety, such as increased access to care and improved patient information accuracy. Conclusions: The findings indicate that this innovative patient feedback on safety intervention is feasible for scale-up to a larger effectiveness trial and further spread into policy and practice. This intervention complements existing safety improvement strategies and activities, and integrates into current patient feedback service requirements for Australian primary care. Further research is needed to examine the intervention effects on safety incident reduction.